Starting from Nina: The Poetic Soul of Paulo Freire - Hall, Budd; Barndt, Deborah; Jackson, Edward; Martin, D'Arcy; Thomas, Barbara (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
This is a collaborative and co‑authored article exploring the poetics of the work of Paulo Freire, the legendary Brazilian philosopher and educator. All five of the authors are themselves poets or people who have used poetry in their work as adult educators and facilitators of social justice. We believe that this is the first English‑language publication of the poem “Recife Forever,” written by Freire himself about the city of his birth. It was written in Chile during his years of exile by the Brazilian dictator.